Homo oeconomicus. Paradigma, critiche, revisioni - CARUSO, SERGIO (Studi e saggi, 2012)
Pantaleoni and Pareto re-established economic theory on the basis of homo oeconomicus which, despite criticisms, went on to become a strangely popular concept, not only among economists, but even in common parlance, where it has assumed a confusing variety of meanings. With a view to setting things in order, this book distinguishes: the methodological hypotheses, which could possibly be corrected on the basis of new economic psychology; the weak anthropologies, retrievable as 'given abstractions' within typical contexts; and finally the extreme versions, that reduce human nature to absolute egoism. The author makes a radical criticism of the latter, drawing upon the extensive tools derived from psychology, philosophical anthropology and political philosophy, and thus succeeds in demonstrating their lack of empirical foundation, their conceptual inconsistency and their ideological dangerousness.